To Express or to Hide: Exploring Vocational High School Students’ Perception Towards Storytelling Strategy in English Classroom - Lestari, Zubaedah Wiji; Dzakir, Muhamad Muflih; Ruswandi, Riki (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2024)
Speaking abilities are seen as crucial ability that students must possess. Many students, however, stay away from communicating in the target language due to a variety of causes. Because of the monotony of the educational procedure, many students are unmotivated to learn to speak. Students require a motivating alternative method to improve their speaking skills. As a result, storytelling is seen as an effective teaching approach. To share a story, storytelling combines a spoken narrative, several digital images, a soundtrack, and modern technologies. As a result, the purpose of this study is to assess vocational high school students' attitudes on the employment of storytelling strategies. This research used mixed method research with 26 participants of the XI class at one state Vocational School in Bandung. The research instruments were questionnaires and interviews. According to the findings of questionnaires and interviews, storytelling can motivate students to learn English, particularly in Speaking. Because storytelling is delivered in a captivating and intriguing manner, it can be an effective technique for teaching speaking. As an alternative approach for learning English, storytelling is recommended.